2009
DOI: 10.1094/mpmi-22-9-1160
|View full text |Cite
|
Sign up to set email alerts
|

Three Combined Quantitative Trait Loci from Nonhost Lactuca saligna Are Sufficient to Provide Complete Resistance of Lettuce Against Bremia lactucae

Abstract: The nonhost resistance of wild lettuce (Lactuca saligna) to downy mildew (Bremia lactucae) is based on at least 15 quantitative trait loci (QTL), each effective at one or more plant developmental stages. We used QTL pyramiding (stacking) to determine how many of these QTL from L. saligna are sufficient to impart complete resistance towards B. lactucae to cultivated lettuce, L. sativa. The alleles of four of the most promising QTL, rbq4, rbq5, rbq6+11, and rbq7 are effective at both the young and adult plant st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 31 publications
2
40
0
Order By: Relevance
“…However, HR responses are also histologically observed in susceptible lettuce and potato cultivars, and are associated with both host and nonhost resistance in potato (Vleeshouwers et al, 2000;Zhang et al, 2009b). Therefore, the presence of responsiveness to an effector in a nonhost does not necessarily mean that this contributes to NHR.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, HR responses are also histologically observed in susceptible lettuce and potato cultivars, and are associated with both host and nonhost resistance in potato (Vleeshouwers et al, 2000;Zhang et al, 2009b). Therefore, the presence of responsiveness to an effector in a nonhost does not necessarily mean that this contributes to NHR.…”
Section: Discussionmentioning
confidence: 99%
“…Microscopic observations on L. saligna inoculated with B. lactucae indicated that NHR is mainly based on prehyphal or prehaustorial resistance. Only malformed hypha-like structures and no haustoria were observed (Lebeda and Reinink 1994;Zhang et al 2009b).…”
Section: Downy Mildew Controlmentioning
confidence: 99%
See 3 more Smart Citations